Diagnostic Challenges in Outpatient Stroke: Stroke Chameleons and Atypical Stroke Syndromes - Wallace EJC (Dove Medical Press, 2021)
Emma JC Wallace, Ava L Liberman Montefiore Medical Center, Albert Einstein College of Medicine, Department of Neurology, Bronx, NY, USACorrespondence: Ava L LibermanMontefiore Medical Center, Albert Einstein College of Medicine, Department of Neurology, 3316 Rochambeau Avenue, 4th Floor, Bronx, NY, 10467, USAEmail avliberm@montefiore.orgAbstract: Failure to diagnose transient ischemic attack (TIA) or stroke in a timely fashion is associated with significant patient morbidity and mortality. In the outpatient or clinic setting, we suspect that patients with minor, transient, and atypical manifestations of cerebrovascular disease are most prone to missed or delayed diagnosis. We therefore detail common stroke chameleon symptoms as well as atypical stroke presentations, broadly review new developments in the study of diagnostic error in the outpatient setting, suggest practical clinical strategies for diagnostic error reduction, and emphasize the need for rapid consultation of stroke specialists when appropriate. We also address the role of psychiatric disease and vascular risk factors in the diagnostic evaluation and treatment of suspected stroke/TIA patients. We advocate incorporating diagnostic time-outs into clinical practice to assure that the diagnosis of TIA or stroke is considered in all relevant patient encounters after a detailed history and examination are conducted in the outpatient setting.Keywords: diagnostic error, stroke chameleons, cerebrovascular disease, stroke